2019
DOI: 10.1103/physrevlett.123.241101
|View full text |Cite
|
Sign up to set email alerts
|

Revival of the Dark Matter Hypothesis for the Galactic Center Gamma-Ray Excess

Abstract: Statistical evidence has previously suggested that the galactic center GeV excess (GCE) originates largely from point sources, and not from annihilating dark matter. We examine the impact of unmodeled source populations on identifying the true origin of the GCE using non-Poissonian template fitting (NPTF) methods. In a proof-of-principle example with simulated data, we discover that unmodeled sources in the Fermi bubbles can lead to a dark matter signal being misattributed to point sources by the NPTF. We disc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
186
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 115 publications
(209 citation statements)
references
References 53 publications
21
186
2
Order By: Relevance
“…While this will not quantitatively change our constraints, it will provide corroborating evidence for the bulge-GCE connection that our analysis clearly prefers. This may be possible through the non-Poissonian template fitting procedure [44][45][46][47][48][49] and wavelet techniques [50][51][52] to detect clustering of photons or radio detection of point sources responsible for the bulge emission [41] or detection of a significant number of millisecond pulsars (putative sources for the bulge gamma-ray emission) with radio telescopes [53][54][55][56].…”
Section: Figmentioning
confidence: 99%
See 1 more Smart Citation
“…While this will not quantitatively change our constraints, it will provide corroborating evidence for the bulge-GCE connection that our analysis clearly prefers. This may be possible through the non-Poissonian template fitting procedure [44][45][46][47][48][49] and wavelet techniques [50][51][52] to detect clustering of photons or radio detection of point sources responsible for the bulge emission [41] or detection of a significant number of millisecond pulsars (putative sources for the bulge gamma-ray emission) with radio telescopes [53][54][55][56].…”
Section: Figmentioning
confidence: 99%
“…Our tests are similar to those carried out in Refs. [45,73]; we have simulated DM injections by taking a random Poisson draw of DM maps generated for a range of DM masses and annihilation cross sections. In particular, we considered self-annihilating DM in thebb channel; DM masses of 10, 25, 100, and 500 GeV; annihilation cross sections in the range ½10 −27 ; 3 × 10 −25 cm 3 =s; and two different DM spatial morphologies (gNFW γ ¼ 1.2 and cored profiles).…”
Section: Appendix E: Dark Matter Injection and Recovery Testsmentioning
confidence: 99%
“…In particular, in ref. [58], it was shown that the non-Poissonian template fit technique utilized in ref. [56] can misattribute smooth gamma-ray signals (such as that predicted from annihilating dark matter) to point source populations.…”
Section: The Galactic Center Gamma-ray Excessmentioning
confidence: 99%
“…Although two groups in 2015 claimed that the data favored the existence of a population of astrophysical point sources which was likely responsible for the Galactic Center gamma-ray excess [56,57], more recent work has shown these results to be problematic. At this point in time, the available gammaray data does not favor the presence of a significant unresolved point source population near the Galactic Center [58,59], revitalizing interest in dark matter interpretations of this signal. The antiproton excess has been a more recent development in the field, and is inherently subject to a larger range of uncertainties than its gamma ray counterpart (arising e.g.…”
Section: Introductionmentioning
confidence: 96%
“…For the indirect DM searches, a number of studies have confirmed an excess of few-GeV gamma-rays from the region around the Galactic center (GC) and suggested that the excess emission could arise from the DM annihilation [18][19][20][21][22][23][24][25][26][27][28][29]. The signal origin of GC excess is not conclusive yet.…”
Section: Jhep07(2020)148 Introductionmentioning
confidence: 99%